Enterprise Architecture Design in Sonic Advertising Company Using TOGAF Framework - Pratama, Yudha; Prasetya, Rusli; Rizki, Muhammad; Anggraeni, Laudiana; Pratiwi, Berliana Wahyu; Meizaroh, Laili; Tarwoto, Tarwoto (International Journal of Informatics and Information Systems, 2024)
This research explores the application of the TOGAF (The Open Group Architecture Framework) framework in designing the enterprise architecture of a Sonic Advertising Company. The study aims to enhance the organizational structure, streamline processes, and optimize technology infrastructure to support the company's business goals and objectives. Through a comprehensive analysis of the current state of the organization, this research proposes a tailored TOGAF-based enterprise architecture design that aligns with Sonic Advertising Company's strategic vision. The findings of this study contribute to the growing body of knowledge in enterprise architecture and provide practical insights for organizations seeking to implement TOGAF in the context of the dynamic advertising industry.